Holistic care for obstructive sleep apnea (OSA) with an emphasis on restoring nasal breathing: A review and perspective. Issue 6 (10th June 2022) - Tsai, Ming-Shao; Chen, Hung-Chin; Liu, Stanley Yung-Chuan; Lee, Li-Ang; Lin, Cheng-Yu; Chang, Geng-He; Tsai, Yao-Te; Lee, Yi-Chan; Hsu, Cheng-Ming; Li, Hsueh-Yu
Abstract : Obstructive sleep apnea (OSA) is characterized by partial or complete airway blockage during sleep. Nocturnal nasal obstruction usually leads to mouth breathing while sleeping, which worsens sleep apnea by aggravating tongue base and lateral pharyngeal wall collapse. The pathogenesis of OSA is multifactorial, and the precipitating factors vary significantly among individuals. Although continuous positive airway pressure (CPAP) is considered the first-line therapy for OSA, its adherence rate remains a challenge. Oral appliances are more suitable for simple snorers or patients with mild OSA. Maxillomandibular advancement (MMA) is highly effective for treating those with mandibular retrognathia and moderate-to-severe OSA. Intrapharyngeal surgeries yield favorable outcomes in patients with large tonsils and low tongue resting position (Friedman Stage I); however, their efficacy declines with time. Each therapy has its own strength and weakness; thus, the principle of multimodality treatment should be adopted. Nasal surgery plays an indispensable role in the holistic care for OSA. In addition to alleviating nasal congestion, nasal surgery significantly reduces snoring intensity and daytime sleepiness, which improves the quality of life of patients with OSA. Although it significantly reduces the respiratory disturbance index, its effect on the apnea–hypopnea index remains controversial. A combination of nasal surgery and multilevel pharyngeal surgery may result in better prognosis. Nasal surgery can significantly reduce the therapeutic pressure and improve the CPAP compliance of patients undergoing CPAP therapy. In conclusion, multimodality treatment and holistic care for OSA should involve nasal surgery for optimizing treatment outcomes.